Education at a glance 2013 : OECD indicators - (:unkn) unknown (OECD Publishing, 2013)
Education at a Glance "provides data on the structure, finances, and performance of education systems in more than 40 countries, including OECD members and G20 partners. Featuring more than 100 charts, 200 tables, and 100 000 figures, 'Education at a Glance' provides key information on the ouput of educational institutions; the impact of learning across countries; the financial and human resources invested in education; access, participation and progression in education; and the learning environment and organisation of schools. In the 2013 edition, new material includes: more recent data on the economic crisis, showing that education remains the best protection against unemployment; more detailed data on programme orientation (general versus vocational) in secondary and tertiary education; an analysis of how work status (full-time, part-time, involuntary part-time) is related to individuals’ level of education; an indicator showing how many of the students who enter a tertiary programme ultimately graduate from it; an indicator on the relationship between educational attainment and two health-related concerns, obesity and smoking". (Verlag, BIBB-Doku)

Contents: Chapter A. The output of educational institutions and the impact of learning Chapter B. Financial and human resources invested in education Chapter C. Access to education, participation and progression Chapter D. The learning environment and organisation of schools
Keywords: G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; G 1.2.2.4 Arbeitslosigkeit; S 1 Stufen der Berufsbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 4.1 Finanzierungsquellen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; T 1.5 International vergleichende Berufsbildungsforschung; Wirtschaftskrise; Jugendarbeitslosigkeit; Bildungssystem; Effizienz; Indikatoren; Bildungsniveau; Bildungsökonomie; Bildungsertrag; Bildungsinvestition; Bildungsausgaben; Bildungsbeteiligung; Bildungsverlauf; Lernbedingungen; Bildungsstatistik; Quantitative Angaben; Internationaler Vergleich; OECD-Staaten